Microwave-Assisted Solvothermal Synthesis and Characterization of M3V2O8 (M = Ca, Cd) Nanoparticles - Sung Lim, Chang (Asian Journal of Chemistry, 2013)
M3V2O8 (M = Ca, Cd) nanoparticles were synthesized successfully using a facile microwave solvothermal route followed by further heat-treatment. Well-crystallized Ca3V2O8 and Cd3V2O8 nanoparticles were formed after heat-treatment at 600 ºC for 3 h showing a fine and homogeneous morphology with particle sizes of 50-150 nm for Ca3V2O8 and 50-200 nm for Cd3V2O8. The synthesized Ca3V2O8 and Cd3V2O8 nanoparticles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and transmission electron microscopy. The optical properties were investigated by photoluminescence emission and Raman spectroscopy.